Proficiency effect on L2 pragmatic competence - Xiao, Feng (Studies in Second Language Learning and Teaching, 2015)
This paper synthesizes cross-sectional studies of the effect of proficiency on second language (L2) pragmatics to answer the synthesis question: Does proficiency affect adult learners’ pragmatic competence? Findings have revealed an overall positive proficiency effect on pragmatic competence, and in most cases higher proficiency learners have higher pragmatic competence. However, increased proficiency does not guarantee a native-like pragmatic performance because proficiency effect varies depending on the nature of target pragmatic features such as types of speech acts (degrees of directness and conventionality) (e.g., Cook & Liddicoat, 2002; Félix-Brasdefer, 2007), modalities of pragmatic performance (comprehension and production) (e.g., Bradovi-Harlig, 2008, 2009), social variables involved in task situations, such as social status (e.g., Allami & Naeimi, 2011), social distance (e.g., Maeshiba, Yoshinaga, Kasper, & Ross, 1996), and power relationship (e.g., Al-Gahtani & Roever, 2012). Moreover, proficiency effect is mediated by contextual variables such as length of stay in the target language community (e.g., Shardakova, 2005; Taguchi, 2011, 2013; Xu, Case, & Wang, 2009).